Cardio-ankle vascular index (CAVI) differentiates pharmacological properties of vasodilators nicardipine and nitroglycerin in anesthetized rabbits - Tatsuo Chiba; Mari Yamanaka; Sachie Takagi; Kazuhiro Shimizu; Mao Takahashi; Kohji Shirai; Akira Takahara (Elsevier, 2015)
Cardio-ankle vascular index (CAVI) has been developed for measurement of vascular stiffness from the aorta to tibial artery, which is clinically utilized for assessing the progress of arteriosclerosis. In this study, we established measuring system of the CAVI in rabbits, and assessed whether the index could reflect different pharmacological actions of nitroglycerin and nicardipine on the systemic vasculature. Rabbits were anesthetized with halothane, and the CAVI was calculated from the well-established basic equations with variables obtained from brachial and tibial blood pressure and phonocardiogram. Nicardipine (1, 3 and 10 μg/kg, i.v.) decreased the blood pressure, femoral vascular resistance, and heart-ankle pulse wave velocity (haPWV). Meanwhile, no significant change was detected in the CAVI at the low or middle dose, which reflects the defining feature of the CAVI that is independent of blood pressure. The index increased at the high dose. Nitroglycerin (2, 4 and 8 μg/kg, i.v.) decreased the blood pressure, femoral vascular resistance, and haPWV. Meanwhile, the CAVI was decreased during the nitroglycerin infusion, which may reflect its well-known pharmacological action dilating conduit arteries. These results suggest that the CAVI differentiates the properties of these vasodilators in vivo.